Sjögren’s Syndrome: Concerted Triggering of Sicca Conditions - Zygmunt Mackiewicz; Justyna Mażul; Ieva Narkevičiūtė; Irena Dumalakienė; Irena Butrimienė; Rita Vilienė; Indrė Stankevičienė; Diana Mieliauskaitė (Journal of Immunology Research)
Aim. The aim of this study was to evaluate the expression of persistence of mumps virus and some cells that interact with viral infection in the focus of the autoimmune epithelitis and peripheral blood of Sjögren’s syndrome patients in comparison to patients with rheumatoid arthritis (RA) and nonautoimmune sicca syndrome (nSS). Materials and Methods. 126 patients (119 women and 7 men) were grouped into four groups: (1) patients with primary Sjögren’s syndrome (pSS), (2) patients with secondary Sjögren’s syndrome due to rheumatoid arthritis (sSS), (3) patients with rheumatoid arthritis (RA), and (4) patients with nonautoimmune sicca syndrome (nSS). Immunohistochemical analysis of immune response to the suggested silent persistence of mumps virus in the minor labial salivary gland biopsies and flow cytometric analysis of blood cells was done. Results. Immunohistochemical signs of mumps virus persistence were found in the minor salivary glands of all study groups. Also, a significantly different immune response to virus infection (protein IFI16, interferons gamma and beta, dendritic cells, and receptor for natural killers) was revealed in the minor salivary glands of the study groups. Cytometric analysis of the blood cells revealed a dropping amount of circulating natural killers and dendritic cells in patients with SS. Significant correlations between immunohistochemical staining and serological findings were revealed. Conclusions. Abundant immunohistochemical signs of mumps virus protein in the salivary glands and depletion of circulating immune cells make a background for thought of presumable mumps or/and other virus participation in epithelial damage causing sicca syndrome in predisposed patients.